Critical discourse Analisis Pesan Dakwah dalam Web Series Demi Masa di Kanal Youtube Kahfeveryday (Analisis Wacana Kritis) - Farida, Diah Ayu (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2024)
The Demi Masa web series is one of the web series in Indonesia produced by the skincare brand "Kahf", this series aims to revive the spirit of doing good and remembering Islamic teachings. This study aaims to find out how the messages of da'wah are in the Demi Masa series. the research methode uses a qualitative descriptive method. The data source for this study was obtained from the da'wah discourse on the web series entitled Demi Masa which was released in March 2024. The data collection technique was carried out by documentation, observing, and taking notes. The data alaiysis technique used in this study is critical discourse analysis ofVan Dijk's theory consisting of levels, namely macrostructure, superstructure, and microstructure. Based on the results of this study, several scenes or dialogues were obtained that contained da'wah messages in the series. In text analysis, da'wah messages tend to be represented in the words and actions of the characters. At the level of social cognition, it reflects an integrative effort to educate, inspire, and influence the audience through stories that are close to their lives. At the level of social context, it can be seen through the responses and comments of the audience on the YouTube platform. The discourse is presented in a persuasive form, so as to raise awareness to make the best use of time, worship, do good deeds, and help others who need help.